Senam Lansia terhadap Tekanan Darah pada Lansia dengan Hipertensi - Lina Safarina; Neng Fuji; Andria Pragholapati (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of elderly exercise on blood pressure in the elderly with hypertension. The method used is a pre-experimental design with one group pre-test and post-test. The results showed that the mean systolic blood pressure before the elderly exercise intervention was 160.00 mmHg, with a standard deviation of 8.083. While the mean value of systolic blood pressure after the elderly exercise intervention was 131.77 mmHg with a standard deviation of 4.799. On diastolic blood pressure, it was found that the mean value of diastolic blood pressure before the elderly exercise intervention was 88.92 mmHg with a standard deviation of 6.211. The results of diastolic blood pressure showed that the average value of diastolic blood pressure after the elderly exercise intervention was 82.31 mmHg with a standard deviation of 3.276. The analysis showed that systolic and diastolic blood pressure decreased with a systolic value = 0.001 and a diastolic value = 0.001. In conclusion, there is an effect of elderly exercise on blood pressure in older adults with hypertension after elderly activity in RW 16 and Posbindu Kenanga Work area of ​​Cipageran Health Center, both systolic and diastolic. Keywords: Hypertension, Elderly, Elderly Gymnastics